(untitled) (Research, Society and Development, 2021)
The pandemic caused by COVID-19 brought a great concern to the population and its governments, as its spread is accelerated. In this context, a safe and effective treatment becomes urgent to treat and reduce probable complications, which can reduce the mortality caused by the disease. Drugs such as chloroquine and hydroxychloroquine began to be tested, these drugs were previously used around the world in the treatment of malaria and rheumatologic diseases. The study aims to analyze the consumption of medicines that underwent changes in their health regulations during the COVID-19 pandemic. An exploratory, retrospective descriptive study was carried out, and the methodological procedure was documentary in the evaluation of sales records of a drugstore in Teresina – PI. Therefore, it was found that during the study period, total sales equal to 5,526 of the drugs ivermectin, nitazoxanide and hydroxychloroquine were made. The results show a variation in drug sales, influenced by the increase and reduction of fatal cases at COVID-19. The use of these medications without a prescription from a qualified professional can cause serious damage to health and may even lead to death.